Histopathological study of lung in autopsy cases: a prospective study - G., Selvambigai; S., Amudhavalli; D., Deepak Chakravarthi C.; S., Ravi (International Journal of Research in Medical Sciences, 2016)
Background: Present days the air pollution and other environmental inhalants, chemical cum toxic substances become uncontrollable. The lungs are involved in a number of infectious, inflammatory and occupational diseases. But involved in almost all cases of terminal events due to cardiovascular causes. Autopsy is an important tool in identifying the cause and manner of death and hence to establish the preventive methods. The aim of this study was to analyse the findings by the histopathological examination in lung tissue received in autopsy specimens. Methods: This study is a prospective study done on 100 autopsy cases received in the Department of Pathology, Chengalpattu medical College for a period of 6 months during July to December 2013. Gross findings were noted during autopsy and specimen was subjected to routine processing and Hematoxylin and Eosin Stain. Histopathological findings were noted. Results: Of the 100 cases, 40% shows pneumonia, 28% shows congestion, 16% shows emphysema, 2% shows normal finding. 14% cases show overlapping. Males were more commonly affected than females. Conclusions: From this study of autopsy specimens of lung the most common findings were pneumonia, emphysema, and congestion. Pneumonia was found to be the most common finding in the study. We should plan to prevent the causes and reduce the prevalence of pneumonia. Educational counseling should be given on exposure of environmental pollutants to the people.